First clinical experience with KODEX-EPD: a novel dielectric imaging and navigation system for catheter ablation. (25th November 2020) - Abeln, B.G.S; Simmers, T.A; Maarse, M; Van Dijk, V.F; Wijffels, M.C.E.F; Balt, J.C; Boersma, L.V.A; Dekker, L.R.C
Abstract: Background: Current electroanatomic mapping systems for catheter ablation often require pre-procedural cardiac imaging, and special catheters. KODEX-EPD is a novel open-platform system that uses dielectric imaging to provide real-time, high-resolution cardiac images, with a potential for tissue characterisation and wall thickness to guide ablation. Purpose: We report our initial experience with the KODEX-EPD system. Methods: The KODEX-EPD uses body surface patches ("sensors") to emit and receive radiofrequency waves across the thorax. Anatomical structures cause gradients in the electrical field, which are measured by a standard electrophysiology catheter and used to generate an anatomical shell of the cardiac chambers. The system requires no direct physical surface contact or fluoroscopy to acquire anatomical information. If direct physical surface contact is added, a voltage map can be created. After mapping with the KODEX-EPD, ablation was continued according to standard of care using radiofrequency or cryoablation. Results: Since November 2019, 26 patients were included (mean age 57.7 (±13.2), 16 (61.5%) male). Ablations were performed for atrial fibrillation in 13 (50.0%) patients, atrial flutter in 10 (38.5%), atrial tachycardia in 1 (3.8%), AVNRT in 1 (3.8%), AVRT in 2 (7.7%) and ventricular extrasystole in 2 (7.7%). The median procedure time was 99.5 [68.8; 112.3] minutes, and fluoroscopy time 14.4 [10.0; 16.9] minutes. All procedures were successful. No adverse events occurred during follow up. Conclusion: KODEX-EPD is a novel electroanatomic system for cardiac mapping as well as anatomical imaging that can be safely and effectively utilised for a variety of cardiac arrhythmia ablations. Future versions will allow wall thickness measurement and lesion quality to optimise the ablation process. Funding Acknowledgement: Type of funding source: None